ByzRev 07.2025.024: Marica Cassis, Medieval Archaeology in the East Roman World: (Past Imperfect). Leeds: Arc Humanities Press 2024. - Böhlendorf-Arslan, Beate (The Byzantine Review, 2025)
Marica Cassis, Medieval Archaeology in the East Roman World (Past Imperfect). Leeds: Arc Humanities Press 2024. x, 112 pp. – ISBN 978-1-64189-219-3 (paperback), e-ISBN 978-1-80270-202-6 (pdf), ISBN 978-1-80270-203-3 (ebook)